Perbedaan Keefektifan Model Pembelajaran Kooperatif Tipe STAD (Students Teams Achievement Division) dan Jigsaw Terhadap Kemampuan Pemecahan Masalah pada Pembelajaran Fisika - Ana Silfiani Rahmawati; Yasinta Embu Ika (Department of Physics Education, Universitas Mataram, 2020)
The purpose of this study is to find out: (1) whether there is an effectiveness of the STAD learning model for solving science problems (Physics); (2) is there an effectiveness of the Jigsaw learning model for problem solving in Natural Sciences (Physics); and (3) whether there is an effectiveness of the STAD and Jigsaw learning models in solving science (Physics) problems. This research is a quantitative study using quasi-experimental design. The research sample consisted of students in class VIIIa and VIIIb of SMP Negeri 2 Ende, while the object of this study was the influence of STAD learning, the influence of Jigsaw learning, and the problem-solving ability of students. Data collection is done through tests and observations. The research instrument consists of objective tests for problem solving skills. Data analysis using one sample test and different test. The results showed that the problem-solving ability of students at SMPN 2 Ende experienced differences between the three learning above. Can be seen in the total difference in the STAD method of 7552,000; for the Jigsaw 8438,000 method; and for the conventional model of 4405,000. This proves that the Jigsaw type cooperative model is more effective than the STAD type cooperative model and conventional learning model, while the STAD type cooperative model is more effective than conventional.